Fruit Characteristics a d Productivity of Date Palm as Affected by GrORegulators - Aljuburi, Hameed J; Al-Masry, Hasan H; Basnna, M Al (Annals of Arid Zone, 2016)
Relative effectiveness of GA3, NAA, ethephon and a mixture of growth regulators on some fruit characteristics and fruit yield of date palm cuitivar "Fardh" was studied. Five uniform female date palm trees were pollinated between 5 and 15 March during I 994, I995 and 1996 by placing eight fresh male strands on female spadix center (flower cluster). Ten female flower clusters were used on each tree, and every. two flower clusters were subjected to one of the followin treatments: control (water), 150 mg L-] GA3, 100 mg L-] NAA, 1000 mg Lethephon and a mixture of growth regulators. Application of ethephon on flower clusters had no significant effect on fruit characteristics and productivity of trees. Naphthalene acetic acid, mixture of growth regulators or GA3 application on "Fardh" flower clusters, reduced fruit dry matter percentage, total soluble solid (OB), fruit ripening percentage, and increased the fruit weight per bunch and per tree. Spraying Fardh date palm flower clusters with J"AA or mixture of growth regulators, 20 days after pollination, were .more effective in reduction of fruit total soluble solids, dry matter percentage, fruit ripening and increasing the fruit yield. Therefore, these treatments could be recommended.